A Study of the Impact of Parental Support on the Student’s Academic Achievement in Selected Primary Schools in Indonesia - Siti Salmah; Angela Syafriani; Linda Sari Bulan Siregar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
This study aimed to examine how parents support their children’s learning process. This phenomenological qualitative study was conducted among six parents of selected primary schools. These parents were divided into three categories; non-working mothers, working mothers, and working fathers. Individual interviews were carried out to collect the data for the study. Results revealed that the parents agreed to and lauded the importance of parental support. However, the results indicated that the parent’s knowledge of parental support differed and their experiences also varied. They faced similar challenges in supporting their children’s learning but developed different strategies to overcome them based on their different social backgrounds, genders, and occupations.